Wilson’s Disease, Etiology and Treatment - Feryal Rada (International Journal of Medical Toxicology and Forensic Medicine)
Background: Wilson’s disease is a chronic, gradually developed disease. Its concern is as an autosomal recessive inherited metabolic disorder. The deposition of copper in many organs, such as the liver, eyes, kidneys, and basal ganglia in the brain is the main cause of this disease. Case Presentation: A 13-year-old male patient was admitted to the Children’s Department in Al-Kadhimae Hospital, Iraq with chief complaints of vomiting, abdominal pain, pallor, icterus, fever, and chest complaints. The laboratory data showed elevated levels of total bilirubin, alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase and reduced levels of globulin (α2 and β), ceruloplasmin, and serum copper. Additionally, high urine copper was reported. After that the patient was diagnosed with Wilson disease and treated with D-penicillamine drug (copper chelation) and zinc acetate tablet. Conclusion: Wilson’s disease is a metabolic error of copper, if undetected and untreated immediately, it causes declining in the function of many organs, such as the liver and brain.